Six Sessions of Sprint-Interval Training Did Not Improve Endurance and Neuromuscular Performance in Untrained Men - Bertschinger, Raphael; Giboin, Louis-Solal; Gruber, Markus (Frontiers in Physiology, 2020)
Previous research demonstrated that six sessions of cycling sprint-interval training (SIT) within a duration of only 2 weeks can increase endurance performance considerably. Primarily muscular mechanisms have been under investigation explaining such performance improvements. However, it has been shown in other exercise tasks that training-induced changes also occur at the level of the central nervous system. Therefore, we hypothesized to observe an enhanced neuromuscular performance in conjunction with an increase in endurance performance after 2 weeks of SIT. Therefore, we randomly assigned 19 healthy men (26 ± 5 years) to a control (n = 10) or a training group (n = 9), the latter performing a replication of the SIT protocol from Burgomaster et al. Before and after the training intervention, both groups performed a cycling endurance test until exhaustion. Neuromuscular function of the right vastus lateralis muscle was assessed before and after each endurance task by the means of maximal voluntary isometric contractions (MVCs). The variables of interest being MVC, voluntary activation was measured by peripheral nerve stimulations (VAPNS), by transcranial magnetic stimulation (VATMS), as well as potentiated resting twitches (Qtw,pot). We did not find any significant differences between the groups in the control variable time to exhaustion in the endurance task. In addition, we did not observe any time × group interaction effect in any of the neuromuscular parameters. However, we found a significant large-sized time effect in all neuromuscular variables (MVC, ηp2 = 0.181; VATMS, ηp2 = 0.250; VAPNS, ηp2 = 0.250; Qtw,pot, ηp2 = 0.304) as well as time to exhaustion ηp2 = 0.601). In contrast to other studies, we could not show that a short-term SIT is able to increase endurance performance. An unchanged endurance performance after training most likely explains the lack of differences in neuromuscular variables between groups. These findings demonstrate that replication studies are needed to verify results no matter how strong they seem to be. Differences over time for the variables of neuromuscular fatigue irrespective of group (MVC, + 9.3%; VATMS, + 0.2%; VAPNS, + 6.3%; Qtw,pot, + 6.3%) demonstrate test-retest effects that should be taken into consideration in future training studies and emphasize the inevitable necessity for controlled experiments.